Prospek Mata Uang BRICS dan Korelasinya Terhadap Potensi Keamanan Ekonomi di Indonesia - Braviano, Victor Ardian Sandi; Heriantomo, Guruh (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This journal examines the potential of the BRICS currency, using the concept of neo-realism and conducting a comparative study on the condition of BRICS economic power. The author uses the Rational choice theory approach to explore the benefits for the BRICS policy to Indonesia, a developing country in the Asian region. The research primarily uses qualitative methods to analyze the process of international politics and the impact of the dollar's hegemony on the economic autonomy of developing countries. The study finds that the emergence of the BRICS currency not only provides a new alternative but also serves as an international preference for developing countries in their efforts to reduce dependence on the dollar. This dedollarization process is centered around the strength of China's renminbi (RMB) currency through the New Development Bank project. While the BRICS currency has not yet rivaled the dollar's hegemony, its implications aim to reduce the IMF's influence on international fund withdrawals, indirectly affecting Indonesia's economic security and regional political stability.